Breastfeeding practices and determinants of exclusive breastfeeding in a cross-sectional study at a child welfare clinic in Tema Manhean, Ghana - Bernard Yeboah-Asiamah Asare; Joyce Veronica Preko; Diana Baafi; Bismark Dwumfour-Asare (International Breastfeeding Journal, 2018)
Abstract Background Exclusive breastfeeding is important for child health and growth, but its practice is low in many developing countries. This study aimed at determining the breastfeeding practices and examining the sociodemographic characteristics that influence exclusive breastfeeding among mothers attending child welfare clinic at Manhean, in the Tema East Sub-Meteropolitan area of Greater Accra region of Ghana. Methods This was a cross-sectional study that employed a structured questionnaire to collect data among 355 mothers of children aged 0–24 months selected through simple random sampling, attending a child welfare clinic from May to June, 2016. Breastfeeding practices were assessed based on the practices in the last 24 h prior to the study as defined by the World Health Organization. Results There was a universal awareness and high knowledge about exclusive breastfeeding among mothers, but prevalence among infants less than 6 months was 66.0% (n = 138/209). Mothers currently breastfeeding were 263 (74.0%); 225 (63.4%) initiated breastfeeding within the first hour after delivery and 289 (81.0%) of the mothers offered colostrum to babies after delivery. Continued breastfeeding rate at 1 year was 77.3% (n = 17/22). Only 33.7% (n = 31/92) of infants aged 6–8 months had started receiving complementary foods. For infants aged less than 24 months, 30.1% (n = 98/326) were bottle feeding. Mothers aged 20–24 (Adjusted odd ratio [AOR] 9.80; 95% confidence interval [CI] 2.11, 45.46), 25–29 (AOR 9.49; 95% CI 2.07, 43.47) and 30–34 (AOR 6.02; 95% CI 1.41, 25.65) were more likely to practice exclusive breastfeeding. Mothers who had tertiary education were less likely to practice EBF than those with no education (AOR 0.18; 95% CI 0.36, 0.85). Mothers from ethnic groups in northern Ghana were less likely to exclusively breastfeed their infants compared to those of Ghanaian (Ga) ethnicity (AOR 0.29; 95% CI 0.09, 0.96). Conclusions Exclusive breastfeeding and timely complementary feeding practices are suboptimal. Educational status, age and ethnicity of mothers strongly predicted maternal practice of exclusive breastfeeding. Interventions emphasizing a practical education should therefore be targeted at addressing factors that influence exclusive breastfeeding.